Advanced manufacturing for transient electronics. (February 2020) - Han, Won Bae; Ko, Gwan-Jin; Shin, Jeong-Woong; Hwang, Suk-Won
Abstract: Abstract : Transient electronics represents recent technology that can partially or completely degrade, dissolve, or disintegrate under certain conditions in actively and passively controlled ways. They offer applications as eco-friendly alternatives to existing electronic components, implantable biomedical devices, and software/hardware protection systems. The degradable characteristics of materials and circuits, however, lead to various fabrication issues and difficulties in manufacturing complex systems requiring fine and elaborate design layouts and microfabrication procedures under thermally and chemically harsh conditions. Identifying advanced materials and the development of manufacturing processes compatible with established transient materials have been conducted for several years to address these issues. In this article, we focus on recent trends in manufacturing technologies for transient electronic systems, including direct fabrication of electronics on transient substrates using organic–inorganic electronic materials, screen-printing approaches particularly for conductive traces, microfabrication combined with multiple transfer-printing techniques, and large-scale, foundry-compatible technologies.